Orignal and fundamental words of Hawrami dialect in Syachamane texts anthropological research (Raparin Journal of Humanities (RJH), 2024)
This research entitled Original and Fundamental Words of Hawrami dialect in Siyachemane Texts that consists two parts. in the first part try to deal with theoretical and historical aspects, and the second part shows the information which obtained from the practical aspect through the researcher’s participation and staying with the research community based on the knowledge of the theoretical aspect of the research.In today’s world culture has its own significance in the life of society. Language as a main element has also play an important role in making individuals belong to one nation and their ancestors both materially and spiritually. Language is the symbol and identity for the existence of a society, people and nation. In this study, the researcher aims to discuss the role of language in the nation’s art. The local communities of Hawraman have many unique things, especially their own l,anguage and art. Songs in general and Siyachemane songs in particular are an original and ancient culture of the community, which is sung in a pure Hawrami language and its poems, verses and songs are still sung by the artists of the community. This artistic endeavor for the Kurdish nation has an artistic, social, religious, economic, political, values.This research consists of two parts. The first part of the research is about Hawrami dialect in which the theoretical aspects of the research are presented. This part consists of three topics: the first topic is language, the second topic is history of Hawrami language, the third topic is the situation of Hawrami language. The second part is to discuss the art of singing Siyachemane within the framework of the anthropology of art and the field aspects of the research and consists of four topics: The first topic is Siyachemane, the second topic is the way of singing Siyachemane music, the third topic is Siyachemane verses, and the fourth topic is the importance of Siyachemane among its listener part is to discuss the art of singing Siyachemane within the framework of the anthropology of art and the field aspects of the research and consists of four topics: The first topic is Siyachemane, the second topic is the way of singing Siyachemane music, the third topic is Siyachemane verses, and the fourth topic is the importance of Siyachemane among its listeners.